2021
DOI: 10.47059/revistageintec.v11i2.1701
|View full text |Cite
|
Sign up to set email alerts
|

Fake Job Detection and Analysis Using Machine Learning and Deep Learning Algorithms

Abstract: With the pandemic situation, there is a strong rise in the number of online jobs posted on the internet in various job portals. But some of the jobs being posted online are actually fake jobs which lead to a theft of personal information and vital information. Thus, these fake jobs can be precisely detected and classified from a pool of job posts of both fake and real jobs by using advanced deep learning as well as machine learning classification algorithms. In this paper, machine learning and deep learning al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The real-time dataset that was used was the meteorological dataset. The input dataset for the proposed study is the meteorological dataset, which was downloaded as CSV files from kaggle.com (Anita et al 2021). "Fraud characteristics," "Business profile," "Required experience and education," "Fraudulent," "Functions," "Benefits," "Description," and "Company Logo" were the major parameters utilized to increase accuracy (%).…”
Section: Methodsmentioning
confidence: 99%
“…The real-time dataset that was used was the meteorological dataset. The input dataset for the proposed study is the meteorological dataset, which was downloaded as CSV files from kaggle.com (Anita et al 2021). "Fraud characteristics," "Business profile," "Required experience and education," "Fraudulent," "Functions," "Benefits," "Description," and "Company Logo" were the major parameters utilized to increase accuracy (%).…”
Section: Methodsmentioning
confidence: 99%
“…Several databases and other online resources were browsed for literature on related topics in order to better understand the techniques and data analysis used. The study of Anita et al (2021) used logistic regression (LR), k-nearest neighbor (k-NN), Random Forest (RF), and deep learning (DL) algorithms for detecting fraudulent jobs from a large pool of real data and found that DL performed best. Another study by Tabassum et al (2021) applied seven different ML algorithms and found the highest accuracy of two classifiers at 95.17%.…”
Section: Related Workmentioning
confidence: 99%
“…The organizations trap the young talent to defraud them of their money and personal information ( Ranparia, Kumari & Sahani, 2020 ). In this way, cybercriminals collect applicants’ information to resell or use later for their purposes ( Anita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%